2006
DOI: 10.1149/1.2196002
|View full text |Cite
|
Sign up to set email alerts
|

XPS, Static SIMS and NEXAFS Spectroscopic Investigation of Thiol Adsorption on Metals and Metal Sulfides

Abstract: Examples are presented of the complementary nature of conventional XPS, synchrotron XPS, ToF-SIMS and NEXAFS spectroscopy when applied to the adsorption of MBT on metals and metal sulfides. Conventional XPS could detect chemisorption via S 2p spectra, detect the onset of multilayer formation via the relevant metal Auger or core level photoelectron spectra, and determine metal thiolate stoichiometry from thick multilayers. Surfaceoptimised synchrotron XPS allowed precise chemisorbed MBT S 2p binding energies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…These signals are also comparable with those reported for the 3‐amino‐5‐mercapto‐1,2,4‐triazole adsorbed through the triazolering nitrogen (401.3, 400.2, 398.9, and 162.3 eV) 61 . Other example of a monolayer formed from related adsorbate containing S and N as donor atoms present also similarities with what we found in profile 17,62 . Mercaptobenzothiazolate (MBT) adsorbed on gold exhibits S 2p and N 1s spectra with both SAu and NAu binding (chemisorbed S at 162–162.2 eV and interacting N at 398.7 eV) indicating two diverse MBT adsorption geometries, one with monodentate exocyclic sulfur and other with bidentate MBT molecule interacting with S,N‐chelating mode 17 .…”
Section: Resultssupporting
confidence: 87%
“…These signals are also comparable with those reported for the 3‐amino‐5‐mercapto‐1,2,4‐triazole adsorbed through the triazolering nitrogen (401.3, 400.2, 398.9, and 162.3 eV) 61 . Other example of a monolayer formed from related adsorbate containing S and N as donor atoms present also similarities with what we found in profile 17,62 . Mercaptobenzothiazolate (MBT) adsorbed on gold exhibits S 2p and N 1s spectra with both SAu and NAu binding (chemisorbed S at 162–162.2 eV and interacting N at 398.7 eV) indicating two diverse MBT adsorption geometries, one with monodentate exocyclic sulfur and other with bidentate MBT molecule interacting with S,N‐chelating mode 17 .…”
Section: Resultssupporting
confidence: 87%
“…The strong coordinating interactions between alkanethiols and metal surfaces have been extensively studied and utilized in the formation of self-assembled monolayers (SAMs) on metal surfaces . It has also been reported that alkanethiols can adsorb onto metal oxide surfaces (such as TiO 2 , ZnO, , and SnO 2 ) and semiconductor substrates (such as InP, , InAs, , and GaAs, , and metal sulfides). Recently, the thiol-metal interaction has been used to immobilize nanoparticles on alkanethiol-modified solid substrates and has been further extended to the colloidal substrates by assembling Au nanoparticles to thiol-functionalized silica colloids. , Philipse et al have explored the attachment of magnetic particles to colloidal silica that was grafted with (3-mercaptopropyl)trimethoxysilane (MPS). , Their efforts, however, have been still limited to only water-soluble γ-Fe 2 O 3 and CoFe 2 O 4 nanoparticles, probably due to the low density of thiol groups achievable during the surface modification of colloidal silica.…”
mentioning
confidence: 99%
“…) and semiconductor substrates (such as InP, 36,37 InAs, 38,39 and GaAs, 40,41 and metal sulfides 42 ). Recently, the thiol-metal interaction has been used to immobilize nanoparticles on alkanethiolmodified solid substrates 43À46 and has been further extended to the colloidal substrates by assembling Au nanoparticles to thiol-functionalized silica colloids.…”
mentioning
confidence: 99%